Chk1 KA1 domain auto-phosphorylation stimulates biological activity and is linked to rapid proteasomal degradation. Issue 1 (December 2018) - Gong, Eun-Yeung; Hernández, Beatriz; Nielsen, Jessica; Smits, Veronique; Freire, Raimundo; Gillespie, David
Abstract The DNA damage-activated protein kinase Chk1 is known to undergo auto-phosphorylation, however the sites and functional significance of this modification remain poorly understood. We have identified two novel Chk1 auto-phosphorylation sites, threonines 378 and 382 (T378/382), located in a highly conserved motif within the C-terminal Kinase Associated 1 (KA1) domain. T378/382 occur within optimal consensus Chk1 phosphorylation motifs and substitution with phospho-mimetic aspartic acid residues results in a constitutively active mutant Chk1 kinase (Chk1-DD) that arrests cell cycle progression in G2 phase of the cell cycle in the absence of DNA damage. Remarkably, the mutant Chk1-DD protein is also subject to very rapid proteasomal degradation, with a half-life approximately one tenth that of wild-type Chk1. Consistent with this, T378/T382 auto-phosphorylation also accelerates the proteasomal degradation of constitutively active Chk1 KA1 domain structural mutants. T378/382 auto-phosphorylation and accelerated degradation of wild-type Chk1 occurs at low levels during unperturbed growth, but surprisingly, is not augmented in response to genotoxic stress. Taken together, these observations demonstrate that Chk1 T378/T382 auto-phosphorylation within the KA1 domain is linked to kinase activation and rapid proteasomal degradation, and suggest a non-canonical mechanism of regulation.